Healthy Partnerships : How Governments Can Engage the Private Sector to Improve Health in Africa - International Finance Corporation (World Bank, 2012)
Health systems across Africa are in urgent need of improvement. The public sector should not be expected to shoulder the burden of directly providing the needed services alone, nor can it, given the current realities of African health systems. Therefore to achieve necessary improvements, governments will need to rely more heavily on the private health sector. Indeed, private providers already play a significant role in the health sector in Africa and are expected to continue to play a key role, and private providers serve all income levels across sub- Saharan Africa's health systems. The World Health Organization (WHO) and others have identified improvements in the way governments interact with and make use of their private health sectors as one of the key ingredients to health systems improvements. Across the African region, many ministries of health are actively seeking to increase the contributions of the private health sector. However, relatively little is known about the details of engagement; that is, the roles and responsibilities of the players, and what works and what does not. A better understanding of the ways that governments and the private health sector work together and can work together more effectively is needed. This Report assesses and compares the ways in which African governments are engaging with their private health sectors. Engagement is defined, for the purposes of this report, to mean the deliberate, systematic collaboration of the government and the private health sector according to national health priorities, beyond individual interventions and programs. With effective engagement, one of the main constraints to better private sector contributions can be addressed, which in turn should improve the performance of health systems overall.